IMPLEMENTASI PEMBELAJARAN BERBASIS MASALAH UNTUK MENINGKATKAN PRESTASI BELAJAR MATEMATIKA SISWA - Eva Wuryani (Program Studi Pendidikan Matematika STKIP PGRI Sidoarjo, 2022)
The purpose of this study was to describe mathematics learning on the subject of equations and inequalities using the Cooperative Method of Problem Based Learning (PBL) Model. The research design used is classroom action research. This study involved 40 students as subjects. The instruments used in this study were evaluation sheets and observation sheets. The results showed that the implementation of the Problem Based Learning Cooperative Method was proven to be able to improve student learning outcomes and also create a more conducive learning atmosphere so that students were more active in participating in lessons and fostered a sense of responsibility in students. complete assignments and group activities.